Online billboard - Kondapaneni, Vikram Kumar (Kansas State University, 2010)
The Online Billboard Application provides different kinds of facilities to the users like education, rental, real estate, employment opportunities, cinema, used cars, etc. Administrator adds, modifies and deletes the different categories of information. The application provides an interactive interface through which a user can interact with different areas of the application easily. A report generation feature is provided using Crystal Reports to generate reports based on the criterion of the users. The user can search whether the vacancies are there or not in different courses in different colleges. The rental details of houses in different areas will be provided for the user based on the user's search criteria. The lands information which will be sold in different areas is provided in the Real Estate category. The user can search for different Movies information for booking. The Used-Cars details will also be provided for the user. The information of Vacancies in different companies will be provided for the user based on their search criteria. The working of the application is made convenient and easy to use for the end user.
Keywords: online billboard; classifieds; Computer Science (0984)